Exercise training in the management of overweight and obesity in adults: Synthesis of the evidence and recommendations from the European Association for the Study of Obesity Physical Activity Working Group. (2nd June 2021) - Oppert, Jean‐Michel; Bellicha, Alice; van Baak, Marleen A.; Battista, Francesca; Beaulieu, Kristine; Blundell, John E.; Carraça, Eliana V.; Encantado, Jorge; Ermolao, Andrea; Pramono, Adriyan; Farpour‐Lambert, Nathalie; Woodward, Euan; et al.
Summary: There is a need for updated practice recommendations on exercise in the management of overweight and obesity in adults. We summarize the evidence provided by a series of seven systematic literature reviews performed by a group of experts from across Europe. The following recommendations with highest strength (Grade A) were derived. For loss in body weight, total fat, visceral fat, intra‐hepatic fat, and for improvement in blood pressure, an exercise training program based on aerobic exercise at moderate intensity is preferentially advised. Expected weight loss is however on average not more than 2 to 3 kg. For preservation of lean mass during weight loss, an exercise training program based on resistance training at moderate‐to‐high intensity is advised. For improvement in insulin sensitivity and for increasing cardiorespiratory fitness, any type of exercise training (aerobic, resistance, and combined aerobic or resistance) or high‐intensity interval training (after thorough assessment of cardiovascular risk and under supervision) can be advised. For increasing muscular fitness, an exercise training program based preferentially on resistance training alone or combined with aerobic training is advised. Other recommendations deal with the beneficial effects of exercise training programs on energy intake and appetite control, bariatric surgery outcomes, and quality of life and psychological outcomes in management of overweight and obesity.